DEMAND FOR MODERN INFORMATION AND COMMUNICATION SYSTEMS IN TOURISM - Meladze, Maia; Jerenashvili, Nino (European Scientific Journal, ESJ, 2012)
Information and Communication Technology (ICT) is one of the key factors of competitiveness. Internet is especially relevant to tourism product since it enables knowledge about a consumer or a tourist to be gathered and vice versa. Tourism product is dominated by the need to provide fast and accurate information to a consumer. Tourist products cannot be examined before traveling. Traveling and tourism industry products do not exist until they are sold. Therefore, the decision on buying trip at the destination is based on the specific information accessible for a tourist. If Georgia does not provide information about tourism sites via Internet, it will be ignored by millions of people who expect that all tourism sites can be accessed via Internet.